Associação de fontes naturais de nitritos e antioxidantes: alternativas para o desenvolvimento de produtos cárneos clean label - Sbardelotto, Paula Regina Rabelo (2022)
With the increase in consumer demand for meat products with reduced synthetic additives, the industry has concentrated efforts on research and development of natural alternatives for these additives, in the quest to meet the demand for clean, clean label labels. The consumption of fresh sausage is high all over the world, considered a cheap and tasty product, manufactured with simple technology, which allows adding value to meat. In this context, this work aims to prepare fresh sausage with the addition of commercial fermented celery extract and rosemary extract with curry in place of the preservative and synthetic antioxidant. For the processing of fresh sausage, six formulations were elaborated, which were designated: control formulation (FC), with preservatives and synthetic antioxidants, being sodium nitrite 0.01% and antioxidant 0.41%, formulation (F1) with added of celery extract 0.1% and rosemary extract with curry 0.01%, formulation (F2) with addition of celery extract (0.14%) and rosemary extract with curry (0.01%) formulation (F3 ) with addition of celery extract (0.1%) and rosemary extract with curry (0.026%), formulation (F4) with addition of celery extract (0.14%) and rosemary extract with curry (0.026%) , formulation (F5) with addition of celery extract (0.12%) and rosemary extract with curry in concentrations (0.018%). The influence of different extracts was evaluated in fresh sausages under refrigeration, through physicochemical analyzes in triplicate (color, pH, proximate composition, texture profile, water activity, determination of nitrite and lipid oxidation). Microbiological analysis (Salmonella, Escherichia coli and mesophilic aerobes) and sensory analysis (flash profile and acceptance test). To assess consumers' perception of meat sausages, the Check-All-That-Apply (CATA) was applied. Fresh sausages produced with fermented celery extract and rosemary with curry showed proximate composition, color and texture properties similar to the control formulation. The use of plant extracts was able to inhibit lipid oxidation at levels below 1 mg/g of malonaldehyde and comply with legislation regarding residual nitrite levels, values below 150ppm, in addition to promoting microbial control during 14 days of storage. at 5°C. Fresh sausages produced with extracts of fermented celery and rosemary with curry performed well in the acceptance test. Red color, characteristic flavor, seasoning flavor and greasy appearance were the most relevant terms in the characterization of fresh sausage samples. The color and appearance of fat were considered important attributes by consumers to characterize the fresh sausage samples. Consumers understand that natural inputs are healthier than synthetic inputs and the intention to pay more for sausages containing natural inputs. The use of natural extracts of fermented celery and rosemary with curry as a substitute for synthetic preservatives and antioxidants is an alternative for fresh sausage formulations with good sensory acceptance by consumers, and may be an option for clean label meat products.